2020
DOI: 10.4103/jmh.jmh_123_19
|View full text |Cite
|
Sign up to set email alerts
|

Association of menopausal symptoms with overweight and obesity among rural middle aged women in North India: A population based study

Abstract: Background: Overweight and obesity are important determinant of increasing morbidity among all age groups, including menopausal women. The symptoms of menopause have a negative impact on the quality of life. Objectives: The aim of this study is to assess the prevalence of overweight and obesity in menopausal women and also to find its association with menopausal symptoms and sociodemographic variables. Materials and Methods: The study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(19 reference statements)
1
5
1
Order By: Relevance
“…The independent factors associated with the prevalence and more severity of MPS in urban and rural women were not exactly the same (Tables 5 and 6). Similar to our results, few studies also showed that a high BMI, low income, no cohabitation partner, low education level, and chronic diseases were demonstrated to be the risk factors for MPS 8,26,31-33 . Body mass index of >28 kg/m 2 is reported to be a risk factor for severe menopausal symptoms 37,38 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The independent factors associated with the prevalence and more severity of MPS in urban and rural women were not exactly the same (Tables 5 and 6). Similar to our results, few studies also showed that a high BMI, low income, no cohabitation partner, low education level, and chronic diseases were demonstrated to be the risk factors for MPS 8,26,31-33 . Body mass index of >28 kg/m 2 is reported to be a risk factor for severe menopausal symptoms 37,38 .…”
Section: Discussionsupporting
confidence: 90%
“…We also demonstrated that the most prevalent menopausal symptoms among both urban and rural women were fatigue (68.19% vs 70.43%), vertigo (59.54% vs 68.63%), and muscle/joint pain (59.32% vs 62.84%); symptoms such as headaches (57.88% vs 61.38%), mood swings (57.42% vs 59.29%), and insomnia (57.21% vs 57.21%) were also frequently reported, which is consistent with previous reports of menopausal symptoms in Chinese women, 8,29,30 which revealed that somatic and psychological symptoms, instead of vasomotor symptoms, were the most common symptoms among Chinese menopausal women. Studies in the southwestern United States, 31 North India, 32 and Cambodia 33 also support this observation. In contrast, the most common symptoms experienced by Spanish and Peruvian urban and rural women were different.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations